2015
DOI: 10.1007/s10509-015-2590-2
|View full text |Cite
|
Sign up to set email alerts
|

Blue outliers among intermediate redshift quasars

Abstract: [Oiii]λ5007 "blue outliers" -that are suggestive of outflows in the narrow line region of quasars -appear to be much more common at intermediate z (high luminosity) than at low z. About 40% of quasars in a Hamburg ESO intermediate z sample of 52 sources qualify as "blue outliers" (i.e., quasars with [OIII] λλ4959,5007 lines showing large systematic blueshifts with respect to rest frame). We discuss major findings on what has become an intriguing field in active galactic nuclei research and stress the relevance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
65
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 61 publications
10
65
1
Order By: Relevance
“…We note that there is a known small systematic offset of δv r ≈ +19 km/s, frequently found in [O III]-strong AGN (e.g., Eracleous & Halpern 2003;Hu et al 2008;Komossa et al 2008;Marziani et al 2016, and references therein). The velocity zero point was set on the peak wavelength of [O III] λ5007, as [O III] λ5007 is a very sharp feature of high S/N, less influenced by the underlying broad Hβ profile.…”
Section: Line and Continuum Fittingssupporting
confidence: 58%
“…We note that there is a known small systematic offset of δv r ≈ +19 km/s, frequently found in [O III]-strong AGN (e.g., Eracleous & Halpern 2003;Hu et al 2008;Komossa et al 2008;Marziani et al 2016, and references therein). The velocity zero point was set on the peak wavelength of [O III] λ5007, as [O III] λ5007 is a very sharp feature of high S/N, less influenced by the underlying broad Hβ profile.…”
Section: Line and Continuum Fittingssupporting
confidence: 58%
“…Harrison et al 2016) samples, it is becoming clear that powerful outflows may be very common in AGN hosts, especially at high redshifts (see e.g. Marziani et al 2016). However, to uncover the kinematics and physical properties of the wind, high-resolution and high S/N observations, such as those presented in this paper, are needed.…”
Section: Discussionmentioning
confidence: 97%
“…It also provides an explanation for the larger blueshifts (v b ) of the CIV with respect to low-ionization emission lines such as MgII and Hβ found at higher luminosities in the "wind-dominated" quasar population (e.g. Richards et al 2011;Marziani et al 2016), and the observed anti-correlation between v b and the EW of the CIV emission line (Korista et al 1998; Krawczyk et al 2013). This SED-based scenario for "wind-dominated" quasars rules out orientation as a major cause of these blueshifts.…”
Section: Discussionmentioning
confidence: 98%